Gut Microbiota and Gastrointestinal Polyps: Unveiling the Causal Connection - Karakan, Tarkan (Turkish Journal of Gastroenterology, 2025)
Cite this article as: Karakan T. Gut microbiota and gastrointestinal polyps: Unveiling the causal connection. Turk J Gastroenterol. 2025;36(5):266-268.